Fresno County Bar Association Witkin Luncheon at Hilton Hotel with Bernard Witkin - Watkins, Howard::::::::: (1987)
Seated: Judge James V. Paige, Bernard E. Witkin, Howard Watkins and Herbert Levy; Presiding Justice George Brown speaking at the lectern and introducing Witkin